Ocular Circulation and Chronic Ocular Ischemic Syndrome before and after Carotid Artery Revascularization Surgery - Shoichiro Kawaguchi; Jun-ichi Iida; Yoshitomo Uchiyama (Journal of Ophthalmology)
Background. We evaluated the effect of carotid revascularization surgery on ocular circulation and chronic ocular ischemic syndrome (OIS). Methods. We examined ninety patients with carotid artery stenosis (more than 50% stenosis) at its origin treated with carotid endarterectomy (N=56) or carotid artery stenting (N=34). Twenty-five patients (28%) complained of chronic OIS. Ocular circulation was examined before and after revascularization surgery using ophthalmic artery (OphAr) and central retinal artery (CRA) color Doppler flow imaging. Results. (1) Ocular circulation: preoperatively, the average OphAr peak systolic flow velocity (Vs) was 0.05 m/sec, and the average CRA Vs was 0.07 m/sec. At 1 week after surgery, the average OphAr Vs significantly increased to 0.32 (P<0.05), and the average CRA Vs significantly increased to 0.11 m/sec (P<0.05). These significant improvements were sustained throughout the three months of the followup. (2) OIS: during the follow-up period (mean: 3.6 years), 15 patients (60%) showed visual acuity improvement, and no patients complained of amaurosis fugax or worsening of the chronic OIS. Conclusion. Carotid revascularization surgery was effective in improving the ocular circulation, and it was also useful for the chronic OIS due to the carotid artery stenosis.